2021
DOI: 10.1002/sd.2164
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for science to support national implementation of the sustainable development goals: A review of progress and gaps

Abstract: The sustainable development goals (SDGs) provide a framework of goals, targets, and indicators designed to guide national implementation of sustainable development to 2030. Several aspects of the framework are challenging, including its complex and integrated scope and transformational character. A range of approaches developed in the sustainability sciences can assist countries to address these challenges. In this paper, we evaluate recent scientific literature as well as national practice relating to the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 110 publications
(226 reference statements)
0
48
0
1
Order By: Relevance
“…Promising developments that could broaden the frameworks applicability include the rapidly evolving literature on subnational interactions (Alcamo et al 2020;Xu et al 2021), increasing emergence of SDG open data portals and citizen science data at subnational levels (Allen et al 2021b;de Sherbinin et al 2021), as well as geospatial data and methods for local stakeholder identification (SDSN et al 2019). Continued developments in these areas offer unprecedented opportunities to enable more data-driven approaches to partnerships.…”
Section: Coalition Building and Data Gapsmentioning
confidence: 99%
“…Promising developments that could broaden the frameworks applicability include the rapidly evolving literature on subnational interactions (Alcamo et al 2020;Xu et al 2021), increasing emergence of SDG open data portals and citizen science data at subnational levels (Allen et al 2021b;de Sherbinin et al 2021), as well as geospatial data and methods for local stakeholder identification (SDSN et al 2019). Continued developments in these areas offer unprecedented opportunities to enable more data-driven approaches to partnerships.…”
Section: Coalition Building and Data Gapsmentioning
confidence: 99%
“…Therefore scientists developed a huge variety of concepts, guidelines, and frameworks as what to governments must consider while implementing the SDGs: Sachs et al (2019) proposed six major transformations to coordinate SDG interventions and concluded that policy coherence is needed across the various branches of government and between levels of government to guide these transformations. In this regards a proposed action agenda for science recommends the development of new tools that help to identify and quantify SDG target interactions as well as monitoring mechanisms to ensure sustainability transformation within the thresholds of the global planetary boundaries (Allen et al 2021;Lu et al 2015). Alternatively, Weitz et al (2015) proposed the adoption of an integrated "biophysical nexus" using, for example, a water, energy and food nexus as the starting point for planning SDG implementation.…”
Section: Synergies and Trade-offs Between Sustainable Development Goals And Targetsmentioning
confidence: 99%
“…This indicates the need to elaborate an in-depth understanding of current methodological approaches to guide the choice toward the best multi-method application for approaching specific cases as well as their related policy challenges and gaps concerned with SDG implementation (Allen et al 2018;Bennich et al 2020;Vacik et al 2014). However, to avoid 'paralysis by analysis', where the different methodological results remain unused, scientists will be required to develop new tools and methods that satisfy policymakers' needs (Allen et al 2021;Lyytimäki et al 2020a, b). The knowledge created and the experiences gathered while implementing SDGs using these approaches should then be made available to scientists, policymakers, and the public on a central web-based knowledge platform such as that presented by Nilsson et al (2018).…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…half way passed. It is possible and necessary to evaluate the results, to determine successes and failures, identifying obstacles to the achievement of the tasks set (Breuer & Leininger, 2021), (Allen et al, 2021). It is clear that a critical approach dominates in statements, since this is how weaknesses are identified, ways to eliminate them are outlined.…”
Section: Introductionmentioning
confidence: 99%
“…Following the course on openness of information, the OECD has developed a methodology -Open, useful and re-usible data 2019 (OURdataindex) (The Center for Open Data Enterprise and Open Data Watch, 2019; Implementing the SDGs during the COVID-19 Pandemic:The index serves for the development and implementation of open data policy at the central level and includes three components: openness of government information and its intention to attract outside actors (1); availability of portals with accessible statistical information (2), monitoring of the openness of government structures(3…”
mentioning
confidence: 99%